Evaluation of energy-saving potential for optimal time response of HVAC control system in smart buildings - Homod R.Z.; Gaeid K.S.; Dawood S.M.; Hatami A.; Sahari K.S. (Elsevier Ltd, 2023)
Controllers; Delay control systems; Energy efficiency; Gradient methods; Intelligent buildings; Membership functions; Optimal systems; Optimization; Response time (computer systems); Semiconductor device manufacture; Thermal comfort; Water craft; Cluster adaptive training; Energy efficient building; Energy saving potential; Fuzzy membership function; Manufacturing industries; Nelder-Mead simplex search; Semiconductor manufacturing process; Temperature and humidities; HVAC; algorithm; building; control system; electronic equipment; energy conservation; manufacturing; residential energy; temporal analysis